Severe Acute Respiratory Syndrome Coronavirus 2 in Farmed Mink ( Neovison vison ), Poland - Rabalski, Lukasz; Kosinski, Maciej; Smura, Teemu; Aaltonen, Kirsi; Kant, Ravi; Sironen, Tarja; Szewczyk, Bogusław; Grzybek, Maciej (Emerging infectious diseases, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the etiologic agent of coronavirus disease and has been spreading worldwide since December 2019. The virus can infect different animal species under experimental conditions, and mink on fur farms in Europe and other areas are susceptible to SARS-CoV-2 infection. We investigated SARS-CoV-2 infection in 91 mink from a farm in northern Poland. Using reverse transcription PCR, antigen detection, and next-generation sequencing, we confirmed that 15 animals were positive for SARS-CoV-2. We verified this finding by sequencing full viral genomes and confirmed a virus variant that has sporadic mutations through the full genome sequence in the spike protein (G75V and C1247F). We were unable to find other SARS-CoV-2 sequences simultaneously containing these 2 mutations. Country-scale monitoring by veterinary inspection should be implemented to detect SARS-CoV-2 in other mink farms.